1996
DOI: 10.1099/13500872-142-5-1123
|View full text |Cite
|
Sign up to set email alerts
|

Ether-bond scission in the biodegradation of alcohol ethoxylate nonionic surfactants by Pseudomonas sp. strain SC25A

Abstract: Pseudomonas sp. strain SC25A, previously isolated for its ability to grow on alcohol ethoxylates (PEG dodecyl ethers) as sole source of carbon and energy, was shown to be capable of growth on the dodecyl ethers of mono-, di, tri-and octaethylene glycols. Comparative growth yields for this series of alcohol ethoxylate nonionic surfactants indicated that, whereas all of the carbon of monoethylene glycol dodecyl ether (MEGDE) was assimilable, only the alkyl chains were assimilated from the higher ethoxamers. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The occurrence of these simultaneous and independent modes of attack has since been confirmed in a pure culture with Pseudomonas sp. strain SC25A [16] and in bench‐scale activated‐sludge systems [10]. Central fission of the test materials used in this study would yield 14 C‐PEGs, which migrate just above the origin, appearing to the far left of the parent in the chromatograms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of these simultaneous and independent modes of attack has since been confirmed in a pure culture with Pseudomonas sp. strain SC25A [16] and in bench‐scale activated‐sludge systems [10]. Central fission of the test materials used in this study would yield 14 C‐PEGs, which migrate just above the origin, appearing to the far left of the parent in the chromatograms.…”
Section: Resultsmentioning
confidence: 99%
“…Mixtures are similarly identified, with x and y designating the range or average chain length and ethoxylate number. Detergent-range LAEs typically encompass C [12][13][14][15][16][17][18] alkyl chain lengths and an ethoxylate range of 1 to 22 units. In 2000, combined production of LAEs in North America and Western Europe exceeded 435,000 metric tons, with approximately 60% being used in household laundry products [1].…”
Section: Introductionmentioning
confidence: 99%
“…This can occur under either anaerobic or aerobic conditions [911]. Although many of the hundreds of surfactants present in household and industrial wastes have been shown to be biodegradable (this includes fluorinated surfactants [11]), there is little information about the type of bacteria responsible for the degradation, or the bacterial biochemistry and catabolic genetics involved; exceptions include some sulfonated surfactants [12–15] and alcohol ethoxylate surfactants [16], where the biochemistry of desulfonation and ether-bond cleavage are well established in certain strains of bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…strain SC25A. [36] The soil-attached bacteria contained a lower proportion of specifically identifiable bacteria, and the proportions ranged from 3.43% to 6.64% (except one experiment where it reached 9.31%, data not shown). The ratio of identified species in all three phyla/subclasses of Proteobacteria among the soil-attached bacteria made up 36.82% to 62.54% of the total attached bacteria.…”
Section: Brij 35 Biodegradation In the Presence Of Phementioning
confidence: 89%